Mensagem dos editores - Menezes Amaral, Carlos Eduardo; Ricci, Éllen Cristina; da Costa Pinheiro, Maria Carolina (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2022)
Mensagem dos editores do número